Combined impact of risk factors on the subsequent development of hypertension. Issue 4 (April 2019) - Huang, Yuli; Deng, Zhihui; Se, Zhen; Bai, Yujia; Yan, Chuanjie; Zhan, Qiong; Zeng, Qingchun; Ouyang, Ping; Dai, Meng; Xu, Dingli
Abstract : Objectives: This study aimed to develop a cumulative score composed of seven risk factors: age, resting heart rate, overweight or obesity, dyslipidemia, hyperuricemia, impaired glucose regulation, and impaired estimated glomerular filtration rate (eGFR), to evaluate the risk of new-onset hypertension. Methods: We retrospectively conducted a cohort study in 23 665 participants free from hypertension at baseline, who attended at least two annual health examinations between 2011 and 2016. We defined hypertension as SBP of 140 mmHg or less and/or DBP of at least 90 mmHg, according to the 2010 Chinese guidelines for the management of hypertension. We computed a composite, individual-level cumulative score incorporating all seven risk factors (no = 0 point; yes = 1 point; total range 0–7 points). Cox regression was used to analyze the association between cumulative score and risk of hypertension. Results: A total of 2305 participants developed hypertension during a median follow-up period of 3.6 years. Compared with participants with 0 points, the adjusted hazard ratios (95% confidence intervals) for the development of hypertension for those with 2, 3, and at least 4 points were 1.61 (1.29–2.02), 2.05 (1.64–2.57) and 2.77 (2.22–3.46), respectively ( P trend < 0.001). This association was present after adjustment for sex and baseline blood pressure. Conclusion: Age, resting heart rate, overweight or obesity, dyslipidemia, hyperuricemia, impaired glucose regulation, and impaired eGFR were associated with significant risk of new-onset hypertension and when combined there was an accumulation of risk.